PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SEND A PROBLEMTERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP NEGERI 3 PARIAMAN - RAHMA SARI LUBIS (Departemen Matematika, 2018)
Mathematical problem solving ability is one of abilities that must have by student in mathematics learning. However, the ability of problem solving of students in class VIII SMP Negeri 3 Pariaman is still low. One of efforts that can be done to solve this problem is to implement model of cooperative learning type send a problem. The purpose of this research is to describe whether mathematical problem solving ability of students who study by cooperative learning type send a problemis better than the ability of students who study by direct learning model. Based on analysis data, it can be concluded that the problem solving ability of students who study by cooperative learning type send a problem modelbetter than the problem solving ability of student who study by direct learning with an error rate 5%. This research showed that, the application of cooperative learning type send a problem model giving an influence on student’s mathematical problem solving ability. Keywords -cooperative learning type send a problem model, direct learning model, ability of mathematical problem solving